User Interfaces (UI) of Machine-to-Machine (M2M) Based Mo-bile Network System for Skilled Construction Workers - Park, Kyungmo; ., . (International Journal of Engineering and Technology, 2019)
The construction industry is more labor-dependent than most other industries. As the competitiveness of construction firms is in part determined by the competence of their workers, most firms endeavor to recruit skilled workers. The South Korean construction industry has declined over the long-term and has had difficulty securing skilled workers, which has increased the number of foreign workers in the country. Accordingly, communication and manpower management related issues have become important, the consequences of which are an increased number of safety-related accidents and quality issues. These problems can be addressed by attracting new proficient labor, improving working conditions, and developing a system to connect existing skilled workers to jobs at construction firms. In this study, a mobile network system was developed to encourage skilled workers to join the construction industry and to be recruited by construction firms.Â Â